Viability of finite element analysis for glenohumeral contact analysis in elite overhead athletes - Goebel, R.; Patel, N.; Haghpanah, B.; Vaziri, A.; Nazarian, A. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Athletes who conduct repeated shoulder motions, (e.g. Handball-, Baseball players), are prone to shoulder joint injuries (1). In these athletes, muscle and capsular tightness has been implicated in subacromial impingement and humeral shift (2). The primary purpose of this thesis is to gain deeper insight into biomechanics of the athletes shoulder through a description of a proof of concept study performed by pairing experimental and computational analysis to examine the effects of posterior-superior capsular tightness on humeral shift on the glenoid during abduction, based on a search to analyze the viability of using finite element (FE) analysis. Method: Capsular plication was analyzed to demonstrate the capabilities of FE analysis. 5 frozen left shoulders from males aged 61 ± 5, were thawed and mounted onto a unique fixture capable of moving the cadaver in 7 degrees of freedom. Tests were conducted by pivoting the joint 60° to 100° in abduction. Reaction forces at the glenohumeral joint were measured, and reflective markers recorded the kinematic data to track the center of rotation of the glenohumeral joint. The FE model was generated using patient specific computed tomography scans. Results: Data shows that plication of the shoulder results in tensile forces in superior-inferior (y-axis) direction compared to compressive force in a normal shoulder. It will also lead to a decrease in tensile force in medial-lateral (z-axis) direction. Loads in the yaxis were different between the two conditions (baseline and plicated) for all arm positions (60°-100°, P < 0.001). Plication resulted in an increase in compression at load cell in sup-inf. plane throughout abduction. Loads in the z-axis were different between the two conditions (baseline and plicated) for three arm positions (70°-90° and P < 0.001). Plication resulted in an increased compression at load cell in med-lat. plane throughout abduction. An insignificant difference in contact area between the two states as sampled occurred. Thus, the plicate state is generating more pressure across the glenoid rather than shifting the humeral head to alleviate the stress accumulation. Conclusion: This study proves the viability in using FE analysis to understand specific and unseen interactions within the glenohumeral joint. A similar method can be utilized to provide pathological understanding, and treatment, to elite overhead athletes with the purpose to reduce shoulder joint injuries.